EVALUATION OF A CAMPUS SERVICE QUALITY RECREATIONAL SCALE - MOKOENA, Bakae Aubrey; DHURUP, Manilal Roy (Studia Universitatis Babeș-Bolyai Oeconomica, 2017)
https://doi.org/10.1515/subboec-2017-0014 In the past two decades, several researchers have applied service quality frameworks in sport-related domains in measuring service quality among participants. However, university campus recreation has been scarce as compared to organised sport at local, regional and national levels, which often depends on a limited tenure linked to their membership as a registered student at a university. The purpose of the study is to investigate service quality dimensions as perceived by university leisure and recreation students. A cross-sectional survey was undertaken among 301 university students using a non-probability purposive sampling. Variables that constituted campus recreation service quality were operationalised through a literature review, including sport and recreational scales. Through factor analysis, seven distinct dimensions of campus recreation service quality were established. These factors were labelled: people interaction, facility design, sociability, physical change, equipment, ambience and program range. Item total correlations show satisfactory convergence of the items within their relevant constructs. This study complements the existing recreational sports body of knowledge by exploring campus recreation service quality. These dimensions may assist campus recreation mangers to understand the dimensions that are pertinent among students within a university context better. Recreation managers, in their periodic measurement of service quality, can incorporate these dimensions. JEL classification: M30, M31, M39.